Evolving city systems - Henry G. Overman; Anthony J. Venables (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper reviews the literature on the forces driving urbanization in developing countries. It presents a model outlining how globalization can lead to the evolution of an urban structure which may approximate Zipf's law. Policy implications are outlined.
Keywords: O10; O18; R10; R12; 330; urbanization; globalization; agglomeration; city systems